Contemporary analysis of functional immune recovery to opportunistic and vaccine‐preventable infections after allogeneic haemopoietic stem cell transplantation. Issue 10 (5th October 2018) - de Silva, Harini D; Ffrench, Rosemary A; Korem, Maya; Orlowski, Eva; Curtis, David J; Spencer, Andrew; Avery, Sharon; Patil, Sushrut; Morrissey, Catherine Orla
Abstract: Objectives: Infections are a major cause of mortality after allogeneic haemopoietic stem cell transplantation (alloHSCT), and immune recovery is necessary for prevention. Novel transplant procedures have changed the epidemiology of infections but contemporary data on functional immune recovery are limited. In this pilot study, we aimed to measure immune recovery in the current era of alloHSCT. Methods: Twenty, 13, 11, 9 and 9 alloHSCT recipients had blood collected at baseline (time of conditioning) and 3‐, 6‐, 9‐, and 12‐months post‐alloHSCT, respectively. Clinical data were collected, and immune recovery was measured using immunophenotyping, lymphocyte proliferation, cytokine analysis and antibody isotyping. Results: Median absolute T‐ and B‐cell counts were below normal from baseline until 9‐ to 12‐months post‐alloHSCT. Median absolute CD4 + T‐cell counts recovered at 12‐months post‐alloHSCT. Positive proliferative responses to Aspergillus, cytomegalovirus (CMV), Epstein‐Barr virus (EBV), influenza and tetanus antigens were detected from 9 months. IL‐6 was the most abundant cytokine in cell cultures. In cultures stimulated with CMV, EBV, influenza and tetanus peptides, the CD4 + T‐cell count correlated with IL‐1β ( P  =   0.045) and CD8 + T‐cell count with IFNγ ( P  =   0.013) and IL‐1β ( P  =   0.012). The NK‐cell count correlated with IL‐1β ( P  =   0.02) and IL‐17a ( P  =   0.03). Median serum levels of IgG1, IgG2 and IgG3 were normal while IgG4 and IgA were below normal range throughout follow‐up. Conclusions: This pilot study demonstrates that immune recovery can be measured using CD4 + T‐cell counts, in vitro antigen stimulation and selected cytokines (IFNγ, IL‐1β, IL‐4, IL‐6, IL‐17, IL‐21, IL‐31) in alloHSCT recipients. While larger studies are required, monitoring immune recovery may have utility in predicting infection risk post‐alloHSCT. Abstract : Infection is a major problem in allogeneic stem cell transplant recipients. Immune‐based risk stratification is required to guide the duration of anti‐microbial prophylaxis administration and timing of re‐vaccination. This proof of concept study demonstrates that immune recovery can be measured using CD4 + T‐cell counts, pathogen specific immune responses and selected cytokines (IFN‐gamma, IL‐1‐beta, IL‐4, IL‐6, IL‐17, IL‐21, IL‐31). Immune parameters measured may have utility in infection‐risk stratification and provides a framework for larger cohort studies.